A Study to Evaluate the Effectiveness of Planned Teaching Program of Environmental Health Among Community People in Selected Rural Area of Gwalior - Arpita Sharma; Mini Anil; Rakesh Kumar (International Journal of Evidence Based Nursing And Practices, 2023)
Context: Environmental health is the subfield of public health that focuses on identifying and altering environmental contributors to illness and injury. The state of the environment in a certain area, especially as it relates to ecological diversity and pollution. The purpose of this research was to evaluate the efficacy of an environmental health education program for the local population. This study follows a quantitative research approach for its methodology. The study used a before-and-after test design. Gwalior’s rural area was the site of the pilot study. The sample was selected using the most practical method. The health of the environment was evaluated using a structured knowledge questionnaire. Fifty students were used for the final study, which included a pre-test and a post-test 7 days later using the same instruments. The data were analyzed using inferential statistics. Mean scores before and after learning about environmental health are displayed. The depicted increase in mean score from pre-test to post-test is 4. The actual percentage of new information gained is 8.125%, with post-test standard deviation (SD) = 3.25, pre-test SD = 4.50, and a paired t-test (p = 2.04) at the 0.05 significance level. The results of the t-test, which compared the data with a predetermined value (= 2.18), demonstrated a significant difference and the efficacy of the planned education program in raising community members' awareness of environmental health at the level of 0.05. At the 0.05 level of significance, the computed “t” value (t = 9.3235) was greater than the table value (t = 2.04). Hence, we may say that H1 was a successful research hypothesis. The results of the study showed that the community members’ understanding of environmental health improved after the planned education program was implemented.
Keywords: Environmental education; evaluation; impact assessment; knowledge acquisition